Poly I: C-activated dendritic cells that were generated in CellGro for use in cancer immunotherapy trials - Fučíková, Jitka; Rožková, Daniela; Ulčová, Hana; Budinský, Vít; Sochorová, Klára; Pokorná, Kateřina; Bartůňková, Jiřina; Špíšek, Radek (Journal of translational medicine, 2011)
BACKGROUND: For clinical applications, dendritic cells (DCs) need to be generated using GMP-approved reagents. In this study, we tested the characteristics of DCs generated in two clinical grade culture media and activated by three maturation stimuli, Poly I: C, LPS and the mixture of proinflammatory cytokines in order to identify the optimal combination of culture media and activation stimulus for the clinical use. METHOD: We tested DCs generation using two GMP-certified culture media, CellGro and RPMI+5% human AB serum and evaluated DCs morphology, viability and capapability to mature. We tested three maturation stimuli, PolyI:C, LPS and the mixture of proinflammatory cytokines consisting of IL-1, IL-6, TNF and prostaglandin E2. We evaluated the capacity of activated DCs to induce antigen-specific T cells and regulatory T lymphocytes. RESULTS: Cell culture in CellGro resulted in a higher yield of immature DCs resulting from increased number of adherent monocytes. DCs that were generated in CellGro and activated using Poly I:C were the most efficient in expanding antigen-specific T cells compared to the DCs that were generated in other media and activated using LPS or the cocktail of proinflammatory cytokines. A comparison of all tested combinations revealed that DCs that were generated in CellGro and activated using Poly I:C induced low numbers of regulatory T cells. CONCLUSION: In this study, we identified monocyte-derived DCs that were generated in CellGro and activated using Poly I:C as the most potent clinical-grade DCs for the induction of antigen-specific T cells.
Keywords: buněčná diferenciace; Epitopes; poly I-C; T-Lymphocytes, Regulatory; Dendritic Cells; regulační T-lymfocyty; Humans; Clinical Trials as Topic; Poly I-C; nádory; Phenotype; Cell Differentiation; imunoterapie; proliferace buněk; Immunotherapy; lidé; fenotyp; Culture Media; klinické zkoušky jako téma; kultivační média; Cell Proliferation; dendritické buňky; epitopy; Neoplasms